Dinâmica da serapilheira e populações de insetos edáficos em florestas secundárias na planície de inundação do alto rio Paraná. - Zviejkovski, Iuli Pessanha (2013)
In many regions of Brazil, the forest biome is characterized mainly by secondary forests, but little is known about their dynamics. The study was conducted on islands in the upper Paraná River floodplain (PR/Brazil), and aimed to evaluate the production and decomposition of litter, as well as variations in the richness and trophic composition of soil insects in areas composed by secondary forests. The areas are consisted by of four old pastures that have been in secondary succession process for 15 years (Mixed forest, Cecropia, Croton and Guava) in descending order of succession and development, besides a fragment of primary forest(Remaining Forest). Litter production was estimated using 10 collectors per area over a period of 13 months, in the years 2009 and 2010, with an average output of 9493.47 kg/ha/year. Thelargest litter fall was after the end of the dry season and early spring (September and October).The input of litter followed a growth pattern according to the advancement of successional stages, does not corroborate the hypothesis of increased production in the early stages of succession. Analysis of litter decomposition was evaluated using litter bags in a period of 120 days, with monthly collections. The decomposition rate was higher for the Remnant Forest, with the highest constant K (0.047 g g^-1 day) and consequently shorter half-life (14 days). The Mixed forest showed the smallest constant k (0.021 g g^-1 day) and longer half-life (33 days), which may be related to a higher C:N ratio observed for this area. There were not significant differences in decomposition rates among the studied areas, reflecting the rapid stabilization of the decomposition environment and nutrient cycling in secondary forests. The soil insects were captured by pitfall traps, totaling 53 morpho-species; Coleoptera was the most abundant order. The hypothesis of increased richness of insects with the advancement of sucesisonal process was not confirmed. The Croton forest was the richest (S = 37) and Guava had the lowest richness (S = 30). As species composition was similar among all successional stages, trophic composition was also similar, offering only in the abundance of each trophic category. According to Chi-Square test, coprophagous and xylophagous were related to forest remnant. For the studied areas, the richness of insects does not seem to be a good indicator of successional development. Based on the species composition and structure of trophic groups, it is possible to indicate those areas of secondary forests, regardless of the structure and richness of its vegetation, showed good evidences indicators of recovery in 15 years of secondary succession. The similarity between some of the parameters analyzed, production and litter decomposition, as well as the composition of soil insects, can be a cause of the homogenizing effect of the floods, an event that decreases the environmental heterogeneity of the floodplain.